2006
DOI: 10.1002/jccs.200600183
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Liquid Crystal Properties of Chiral Compounds Containing the Core Structure of 6‐Hydroxynicotinic Acid or 4‐Hydroxyphenylacetic Acid

Abstract: The carboxylic acid 4‐hydroxybenzoic acid, bonded directly with (R)‐2‐octanol, is the core molecule of chiral liquid crystal (R)‐MHPOBC. This acid was substituted either by 6‐hydroxynicotinic or by 4‐hydroxyphenylacetic acid. Such a structural variation induced a remarkable influence on the liquid crystal properties of (R)‐MHPOBC. The series of compounds 1˜4 containing 6‐hydroxynicotinic acid moiety tend to exhibit a chiral smectic C (SmC*) phase, while the series of compounds 5˜8 containing 4‐hydroxyphenylace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The unique feature of spontaneous polarization (Ps) in FLCs is an important factor for electro-optical applications since liquid crystals with significant polarization are expected to display faster reorientation in an optical light shutter [1]. The physical properties of the ferroelectric phase are dramatically affected by the structure of the FLC compounds [4][5][6]. For example, Dabrowski et al observed that substituting a naphthyl group for the biphenyl group in the FLC compounds reduces the clearing temperature, mesophase transition temperatures, and the phase range of the liquid crystal region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique feature of spontaneous polarization (Ps) in FLCs is an important factor for electro-optical applications since liquid crystals with significant polarization are expected to display faster reorientation in an optical light shutter [1]. The physical properties of the ferroelectric phase are dramatically affected by the structure of the FLC compounds [4][5][6]. For example, Dabrowski et al observed that substituting a naphthyl group for the biphenyl group in the FLC compounds reduces the clearing temperature, mesophase transition temperatures, and the phase range of the liquid crystal region.…”
Section: Introductionmentioning
confidence: 99%
“…1 shows the molecular structures of the four FLC samples used for this study. For the details on the FLC synthesis, please refer to related literature [24][25][26]. The structural difference between the four FLC compounds is mainly in the core and the diastereomeric molecules.…”
Section: Introductionmentioning
confidence: 99%
“…1, the molecular structures of the two FLC samples used for this study are depicted. Please refer to reports [21][22][23] for the details on FLC synthesis. The structural difference between the two FLC compounds was in the diastereomeric molecules.…”
Section: Methodsmentioning
confidence: 99%
“…Of the entire class of liquid crystals, ferroelectric liquid crystals (FLCs) have attracted interest not only in fundamental research but also for their technological application [1][2][3][4]. The spontaneous polarization (Ps), which is dramatically affected by the structure of the FLC compounds [4][5][6], is an important factor in their technological applications.…”
Section: Introductionmentioning
confidence: 99%